Design of a Compact Millimeter Wave Antenna for 5G Applications based on Meta Surface Luneburg Lens - Rao, Karedla Chitambara; Nataraj, Dasari; Chakradhar, K. S.; Ujwala, G. Vinutna; Lakshmunaidu, M.; Dadi, Harihara Santosh (Engineering, Technology & Applied Science Research, 2025)
As the demand for fast and reliable wireless connectivity increases, the 5G technology has emerged as a promising solution. This study focuses on enhancing the gain and return loss performance of 5G wireless communication systems, with a particular emphasis on the Meta Surface Luneburg technique. In this work, a compact millimeter-wave antenna operating at a frequency of 28GHz dedicated to 5G applications is proposed and designed. The introduced design utilizes a metasurface Luneburg technique in order to obtain reduced size, high gain, and less return loss. The proposed antenna is implemented on a 40 × 40 × 0.5 mm3 RT Duroid 5880 Lossy substrate with a relative dielectric constant of εr = 2.2 and a loss tangent of 0.0068. Two-unit cells are strategically arranged in an array on the substrate to form a Luneburg meta-lens, which transforms spherical wavefronts into planar wavefronts. This configuration enables the antenna to achieve a directed beam at 28 GHz. The antenna is simulated, and key parameters, such as gain and return loss are analyzed. The results show that the antenna achieves a gain of 7.9 dBi and a return loss of less than -10 dB, demonstrating its suitability for 5G applications.